Penal practices of partisans in the Kaunas Region (1944–1952). Part II - Miknevičius, Gintautas (Genocidas ir rezistencija, 2021)
Part 1 of this Article analyses campaigns of the partisans in Kaunas county and Kaunas city that took place in 1944-1945. Kaunas county geographically was a midpoint of Lithuania, it bordered the counties of Šakiai, Raseiniai, Kėdainiai, Ukmergė, Trakai (from April 1946 – Kaišiadorys), Alytus and Marijampolė. In 1944 the county consisted of 16 rural districts: Aukštoji Panemunė (164 km2), Babtai (224 km2), Čekiškė (252 km2), Garliava (152 km2), Jonava (418 km2), Kruonis (230 km2), Lapės (115 km2), Pakuonis (122 km2), Pažaislis (71 km2), Raudondvaris (103 km2), Rumšiškės (128 km2), Seredžius (83 km2), Vandžiogala (269 km2), Veliuona (134 km2), Vilkija (152 km2), Zapyškis (117 km2). The territory of this part of the county – 2734 km2. The city of Kaunas is not included, the territory of which – 130 km2. Thus, the entire territory of the county, including the city of Kaunas, occupied 2864 km2. In June 1945, Kaunas county had 24 thousand households and 107 thousand population. In the summer 1945, 86 064 inhabitants lived in Kaunas city.On June the 23rd 1944, the Soviet Army started the Strategic Offensive Operation “Bagration”. During this operation, the German group “Centro” was destroyed. At the beginning of July, Soviet forces – units of the 1st Baltic and 3rd Belorussian Front– invaded the territory of Lithuania. In Kaunas county, the divisions of the 3-rd Belorussian Front were fighting, who reached this county by the end of July. By middle-August, the entire territory of Kaunas county was occupied.The organized partisan warfare against the Soviets in Kaunas county started in November 1944. Already in December it spread throughout the entire county, and Kerinas, who was the head of Kaunas NKVD division, called this phenomenon an uprising against the Soviet authorities. Partisan platoons used to contain up to 100 people, these platoons used to join other groups of partisans. Such platoons used to occupy the centres of rural districts and fight NKVD battalions. In 1944, during campaigns of the partisans, 45 people were killed.NKVD-people, having been intimidated by partisan struggle, organized chekist-military operations, during which they managed to destroy large platoons of partisans, therefore, from the year 1945 on, the partisans changed their tactics and started to use another way of fighting – partisan platoons were divided into groups consisting of 5-10 people and then Soviet repressive bodies encountered difficulties in detecting and destroying platoons of partisans. Mostly, the partisans attacked collaborators with the Soviet authorities, and especially – their military squads. The most famous assault of the partisans in 1945 in Kaunas county, was an attack on Seredžius rural district, during which a military platoon of the collaborators was annihilated totally. In total, during the campaigns of the year 1945, the partisans killed 173 people.
Keywords: Soviet occupation; repressive structures; partisans; punitive politics